The FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU MASYARAKAT DALAM PENCEGAHAN PENYAKIT DBD DENGAN 3M+ DI WILAYAH KERJA PUSKESMAS HARAPAN RAYA 2020.: FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU MASYARAKAT DALAM PENCEGAHAN PENYAKIT DBD DENGAN 3M+ DI WILAYAH KERJA PUSKESMAS HARAPAN RAYA 2020. - Rossa anugerah putri Rossa; Hoppy Dewanto; Nila Puspita Sari (Jurnal Kesehatan Komunitas, 2021)
Dengue fever is an acute an endemic disease caused by dengue virus that is transmitted by aegypti mosquito in urban areas and in rural areas of aedesalbopictus.Who ( 2015 ) % 2,5 billion or 40 percent of the population in the world at risk of dengue fever living chiefly in tropical and subtropical regions. in the work Puskesmas Harapan Raya obtained 182 case in the last years, Found a kind of water body in a state of open garbage and, like a bottle plastic, former canscontaining a puddle where The aedes aegyptimosquito. Research aims to understand the factors that relating to the behavior of the people in the prevention of dengue fever case with 3M Plus in the work area of Puskesmas Harapan Raya 2020. A method of this research is Analytic observational with the design cross sectional and use test chi square. This study was conducted in august 2020, This is all subject of study the people residing in the work area Puskesmas Harapan Raya With a population about 13.750 and the number of samples from the190 people. Sampling techniques used is purposive sampling .The result showed that there is a connection between environmental sanitation:( p value 0,000, the por = 4,426 ), education: (p value 0,010, the por = 2,341 ), knowledge ( p value 0,002 , the por = 2,627 ), Solid waste management ( p value: 0,036, the por = 2,061 ) meaningful relationship with behavior in prevention of the disease with 3m plus It is hoped that the Harapan Raya Puskesmas will carry out counseling on abuse by implementing 3M Plus,Always urge people to maintain clean environment in not letting the thriftdeveloping the dengue